2018
DOI: 10.14334/wartazoa.v27i2.1595
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic and Development of Cow’s Milk Dadih as an Alternate of Buffalo’s Milk Dadih

Abstract: Dadih is a product of fermented buffalo milk in a bamboo tube from West Sumatera. The decline of buffalo population in West Sumatera caused dadih scarcity. The demand of dadih is high because it is an integral part of the Minangkabau's diet and culture. Cow milk can be used as a substitute of buffalo milk for producing dadih, although the product has slightly different characteristics, especially lower total solids. Producing cows milk dadih similar to buffalo milk dadih, fresh cow milk should be concentrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…DNA sequencing results were analyzed using NCBI BLAST. According to Willey et al (2009), 16S rRNA sequencing looks at the similarity of isolates to those already available in GenBank; this is one molecular detection method that is ideal enough to know the kinship relationship between bacteria because the 16S rRNA sequence is a gene found in all microbes The next closest species for which a sequence alignment of at least 100% query coverage was observed were Pediococcus pentosaceus strain DSM 20336, Pediococcus acidilactici strain NGRI 0510Q and Pediococcus argentini strain CRL 776 at 98% similarity to the DS15 isolate. Pediococcus stilesi strain FAIR-E 180 showed 98% similarity with 99% query coverage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA sequencing results were analyzed using NCBI BLAST. According to Willey et al (2009), 16S rRNA sequencing looks at the similarity of isolates to those already available in GenBank; this is one molecular detection method that is ideal enough to know the kinship relationship between bacteria because the 16S rRNA sequence is a gene found in all microbes The next closest species for which a sequence alignment of at least 100% query coverage was observed were Pediococcus pentosaceus strain DSM 20336, Pediococcus acidilactici strain NGRI 0510Q and Pediococcus argentini strain CRL 776 at 98% similarity to the DS15 isolate. Pediococcus stilesi strain FAIR-E 180 showed 98% similarity with 99% query coverage.…”
Section: Resultsmentioning
confidence: 99%
“…Dadih is made from buffalo milk which is fermented in bamboo for 24-48 hours. The fermentation process is carried out by LAB which are naturally present in buffalo milk (Rizqiati et al, 2015) and the environment (Wirawati et al, 2017). Studies have found that, the LAB strains present in dadih are generally Lactobacillus, Streptococcus, Leuconostoc and Lactococcus (Collado et al, 2007;Surono, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The total viable LAB count was in the range of 1.42 × 10 8 -3.80 × 10 8 cfu/g [34]. Various types of LAB can be found from one place to another in West Sumatra [35]. Leuconostoc paramesenteroides, which produce acetic acid, diacetyl, and other volatiles as the aromatic compounds were reported as the predominant strains of LAB [36].…”
Section: Microbiota Of Dadihmentioning
confidence: 99%
“…The main problem in dadih production is the decreasing buffalo milk production due to the decreasing buffalo population in West Sumatra [22,35]. Wirawati et al [35] reported that in 2000, the total population of buffaloes in West Sumatra was 230,818 buffaloes based on Statistics of Sumatera Barat Provinces. In 2015, the population of buffaloes was 121,939 buffaloes [81], and in 2018, the number decreased again to 78,038 buffaloes [82].…”
Section: Challenges and Future Trends Of Dadihmentioning
confidence: 99%
See 1 more Smart Citation